Статистический анализ числа разделений отцепов на стрелках при расформировании составов - Бобровский, Владимир Ильич; Кудряшов, Андрей Вадимович; Ефимова, Л. О. (Днепропетровский национальный университет железнодорожного транспорта имени академика В. Лазаряна, Днепропетровск, 2008)
UKR: Розроблена методика визначення матриці розділень відчепів составу, виконано статистичний аналіз числа розділень та його зв’язку з числом відчепів у составі.

RUS: Разработана методика определения матрицы разделений отцепов состава, выполнен статистический анализ числа разделений и его связи с числом отцепов в составе.

ENG: The procedure of determination of disintegration matrix of the uncoupled parts of a train has been developed. The statistical analysis of a number of disintegrations and its connection with a number of the uncoupled train parts has been also performed.
Статистичний аналіз числа розділень відчепів на стрілках при розформуванні составів
Statistical Analysis of the Cuts Divisions Number on the Arrows at the Dissolution of the Rolling Stocks
В. Бобровский: ORCID 0000-0001-8622-2920; А. Кудряшов: ORCID 0000-0002-5965-3378
Keywords: матриця; состав поїзду; відчеп; матрицa; состав поезда; отцеп; matrix; train; cut; КСВ